Mapping underutilised and emerging food sources and technologies as solutions to food insecurity in South Africa - Lisa-Claire Ronquest-Ross; Gunnar O. Sigge (South African Journal of Science)
There are clear signs that the South African food system is failing as we experience increasing trends in hunger, rising food costs, lack of dietary diversity, child stunting, foodborne illnesses, food waste and an obesity epidemic coupled with malnutrition. A literature review was conducted to identify underutilised or emerging new food sources and technologies (UEFST). They were identified as indigenous African crops (IACs), insects, fermentation, cultured meat and seafood, food waste recovery and algae. Criteria were developed to assess these UEFST to evaluate their ability to provide affordable, nutritious, safe and relevant food for South Africans (ANSSA). A survey was conducted with food professionals from industry, academia and government to evaluate these UEFST against the ANSSA criteria. Findings indicate that the two most promising UEFSTs – IACs and food waste recovery – could be available to South Africans within three to five years. These sources were rated highest in their ability to meet the ANSSA criteria identified. The two underutilised or emerging food sources with the longest time frame to commercialisation were cultured meat and seafood and algae (5 to 10 years), with cultured meat and seafood scoring the lowest of all six UEFST against the ANSSA criteria.